2020
DOI: 10.1038/s41597-020-00614-y
|View full text |Cite
|
Sign up to set email alerts
|

CroSSED sequence, a new tool for 3D processing in geosciences using the free software 3DSlicer

Abstract: The scientific application of 3D imaging has evolved significantly over recent years. These techniques make it possible to study internal features by non-destructive analysis. Despite its potential, the development of 3D imaging in the Geosciences is behind other fields due to the high cost of commercial software and the scarce free alternatives. Most free software was designed for the Health Sciences, and the pre-settled workflows are not suited to geoscientific materials. Thus, an outstanding challenge in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Fusing imaging modalities ( 24 ) with no a priori knowledge or evidence about their optimal combination for the targeted therapy can lead to unnecessary, redundant analysis with a negative effect on the final decision. Thus, clinicians should provide insight and participate in cooperation with the data science engineers regarding specific lesion attributes concerning the followed diagnosis protocols.…”
Section: Development Of Radiomics Prediction Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusing imaging modalities ( 24 ) with no a priori knowledge or evidence about their optimal combination for the targeted therapy can lead to unnecessary, redundant analysis with a negative effect on the final decision. Thus, clinicians should provide insight and participate in cooperation with the data science engineers regarding specific lesion attributes concerning the followed diagnosis protocols.…”
Section: Development Of Radiomics Prediction Modelsmentioning
confidence: 99%
“…The critical issues of the robustness of quantitative features with respect to imaging variations and inter-institutional variability need to be investigated further. Currently, there are several advanced machines equipped with deep learningbased algorithms aimed at contour functions, including the 3DSlicer (24)(25)(26), DeepMind (Google) (27), and Project InnerEye (Microsoft) (https://www.microsoft.com/en-us/ research/project/medical-image-analysis/).…”
Section: Pre-processing Of Informationmentioning
confidence: 99%
“…These 650 patients’ chest CT data were procured from the picture archiving and communication system (PACS). The software 3DSlicer [ 11 ]was used to identify and quantify muscle tissue [ 12 ], which allows for selective visualization of specific tissues, such as muscle or fat tissue, by setting density intervals representing the tissue of interest. According to the current literature, a density range of -29 to + 150 Hounsfield units (HU) was selected.…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of automatic segmentation depends on the algorithm’s precision and capacity to distinguish the ROIs from the surrounding tissues. Automatic segregation can be managed by a variety of technologies [ 45 , 46 , 47 ]. Because of this, numerous studies have demonstrated that semi-automatic segmentation is a more suitable method [ 48 ].…”
Section: Radiogenomics and Its Use In Precision Medicinementioning
confidence: 99%